Essays in financial econometrics - Chaim, Pedro Luiz Paolino (2019)
This dissertation is composed by five self-contained papers on broad themes in financial econometrics. The first two papers are applications of stochastic volatility models with discontinuous jumps to cryptocurrencies. Third and fourth papers deal with strict local martingale theory, one is an investigation regarding the presence of price bubbles in Bitcoin and the other proposes an interpretation for observed systematic forecast errors in Brazilian foreign exchange markets. The fifth and final paper discusses the estimation of long memory stochastic volatility models using integrated nested Laplace approximations